The implications of increased mammographic breast density for breast screening in Jordan. Issue 4 (23rd June 2020) - Al‐Mousa, Dana S.; Alakhras, Maram; Spuur, Kelly M.; Alewaidat, Haytham; Abdelrahman, Mostafa; Rawashdeh, Mohammad; Brennan, Patrick C.
Abstract: Introduction: Mammographic breast density is associated with a four to six times increased risk for breast cancer. Mammographic breast density varies by ethnicity, geographical region and age. The aim of this study was to document for the first time the mammographic breast density of Jordanian women and to explore its relationship with age. Methods: Mammograms completed at King Abdullah University Hospital (Irbid, Jordan) between January 2016 and August 2018 were retrospectively reviewed and classified for breast density using the American College of Radiology (ACR) Breast Imaging‐Reporting and Data System (BI‐RADS). Descriptive analyses and Kurskal–Wallis test were used to examine the association between age and mammographic breast density. Results: A total of 659 mammograms were reviewed. A significant inverse relationship was observed between age and breast density ( P < 0.001). In women aged 40–49 years, 83.2% had dense breasts (ACR BI‐RADS (c) and (d)). This percentage decreased to 59.8% of women aged 50–59 years; 38.4% of women in their 60s and 37.9% of women aged 70 years or older (ACR BI‐RADS (c) only). Conclusion: The mammographic breast density of Jordanian women has been shown to be high across all age groups. Increased mammographic breast density is associated with increased breast cancer risk and renders mammography a less effective technique for the early detection of breast cancer. Breast cancer screening of Jordanian women should be individualised to develop screening protocols and include additional adjunct imaging to best manage women at high risk. Abstract : The mammographic breast density of Jordanian women has been shown to be high across all age groups. Increased mammographic breast density is associated with increased breast cancer risk and renders mammography a less effective technique for the early detection of breast cancer. Breast cancer screening of Jordanian women should be individualised to develop screening protocols and include additional adjunct imaging to best manage women at high risk.